2018
DOI: 10.1519/jsc.0000000000001826
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic Comparison of Barbell Deadlift, Hex Bar Deadlift, and Hip Thrust Exercises: A Cross-Over Study

Abstract: Andersen, V, Fimland, MS, Mo, D-A, Iversen, VM, Vederhus, T, Rockland Hellebø, LR, Nordaune, KI, and Saeterbakken, AH. Electromyographic comparison of barbell deadlift, hex bar deadlift, and hip thrust exercises: a cross-over study. J Strength Cond Res 32(3): 587-593, 2018-The aim of the study was to compare the muscle activation level of the gluteus maximus, biceps femoris, and erector spinae in the hip thrust, barbell deadlift, and hex bar deadlift; each of which are compound resisted hip extension exercises… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
73
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(82 citation statements)
references
References 22 publications
(25 reference statements)
1
73
1
4
Order By: Relevance
“…Surface Electromyography (sEMG) is a technique employed in a vast array of applications from assistive technologies (Scheme and Englehart, 2011a;Phinyomark et al, 2011c) to bio-mechanical analysis (Andersen et al, 2018), and more generally as a way to interface with computers and robots (Zhang et al, 2009;St-Onge et al, 2019). Traditionally, sEMG-based gesture recognition literature primarily focuses on feature engineering as a way to increase the information density of the signal to improve gesture discrimination (Oskoei and Hu, 2007;Scheme and Englehart, 2011b;Phinyomark et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…Surface Electromyography (sEMG) is a technique employed in a vast array of applications from assistive technologies (Scheme and Englehart, 2011a;Phinyomark et al, 2011c) to bio-mechanical analysis (Andersen et al, 2018), and more generally as a way to interface with computers and robots (Zhang et al, 2009;St-Onge et al, 2019). Traditionally, sEMG-based gesture recognition literature primarily focuses on feature engineering as a way to increase the information density of the signal to improve gesture discrimination (Oskoei and Hu, 2007;Scheme and Englehart, 2011b;Phinyomark et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…312 However, in light of the previous research as well as present findings, it appears that multi-joint 313 exercises which include trunk extension (such as the BBS and BHT) are not sufficient to strengthen the 338 might be that analyses of individual angles would reveal angle specific strength increases -particularly 339 at 0˚ (full extension) where the hip thrust exercise might have provided the greatest activation of the 340 lumbar extensors (e.g. at 180˚ during a BHT exercise; Andersen, et al 2018). Future research might 341 consider sufficient sample sizes and power to examine this as a pre-specified hypothesis.…”
mentioning
confidence: 48%
“…The authors reported favourable effect sizes for the BHT for 80 10m and 20m sprint times, and isometric mid-thigh pull, whereas the front squat exercise produced 81 favourable effect sizes for the vertical jump and front squat 3RM. Andersen, et al (2018) compared EMG 82 activity during the barbell deadlift, hex bar deadlift and BHT exercises. Although there were no 83 statistically significant differences between the three exercises for erector spinae muscle activation, the 84 BHT did elicit the greatest muscle activation during the concentric phase of the movement when the hip 85 angle was approaching or exceeding 180 degrees.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors reported favourable effect sizes for the BHT for 10m and 20m sprint times, and isometric mid-thigh pull, whereas the front squat exercise produced favourable effect sizes for the vertical jump and front squat 3RM. Andersen, et al (2018) compared EMG activity during the barbell deadlift, hex bar deadlift and BHT exercises. Although there were no statistically significant differences between the three exercises for erector spinae muscle activation, the BHT did elicit the greatest muscle activation during the concentric phase of the movement when the hip angle was approaching or exceeding 180 degrees.…”
Section: Introductionmentioning
confidence: 99%